University Lecturers and Students Could Help in Community Education About SARS-CoV-2 Infection in Uganda. (July 2020) - Echoru, Isaac; Kasozi, Keneth Iceland; Usman, Ibe Michael; Mutuku, Irene Mukenya; Ssebuufu, Robinson; Ajambo, Patricia Decanar; Ssempijja, Fred; Mujinya, Regan; Matama, Kevin; Musoke, Grace Henry; Ayikobua, Emmanuel Tiyo; Ninsiima, Herbert Izo; et al.
Background: The World Health Organization has placed a lot of attention on vulnerable communities of Africa due to their chronically weak health care systems. Recent findings from Uganda show that medical staff members have sufficient knowledge but poor attitudes toward coronavirus disease 2019 (COVID-19) pandemic. Aim: The aim of this study was to determine the knowledge, attitudes, and preparedness/practices of lecturers and students in the fight against COVID-19. Method: This was a descriptive cross-sectional study of 103 lecturers and students both men and women of age group 18 to 69 years in western Uganda. Data were obtained through a pretested questionnaire availed online. Results: Knowledge on COVID-19 symptoms was highest in this order: fever > dry cough > difficulty breathing > fatigue > headache with no significant differences between lecturers and students. Knowledge of participants on transmission of COVID-19 was highest in the order of cough drops > contaminated surfaces > person-to-person contact > asymptomatic persons > airborne > zoonotic with no significant differences among lecturers and students. Lecturers and students were all willing to continue using personal protective equipment like masks, and personal practices such as covering the mouth while sneezing and coughing, no handshaking, and washing of hands with no significant differences in the responses. The positive attitudes that COVID-19 could kill, anyone can get COVID-19, and willing to abide by the set regulations against the pandemic showed personal concerns and desired efforts against COVID-19. Conclusion: The study identifies lecturers and students as potential stakeholders in the fight against community transmission of COVID-19.